Synthesis of Long-Chain Branched Polyolefins by Coordinative Chain Transfer Polymerization - Lee, Hyun Ju; Baek, Jun Won; Kim, Tae Jin; Park, Hee Soo; Moon, Seung Hyun; Park, Kyung Lee; Bae, Sung Moon; Park, Jinil; Lee, Bun Yeoul (Macromolecules, 2019)
Synthesis of long-chain branched polymers has been a crucial concern in the polyolefin industry. In this study, a method to produce long-chain branches (LCBs) in coordinative chain transfer copolymerization (CCTcoP) is suggested. A dialkylzinc compound bearing vinyl groups ((9-decenyl)2Zn) is prepared, which works well not only as a chain transfer agent but also as a comonomer in CCTcoP, resulting in the generation of LCBs. The generation of LCBs is confirmed by gel permeation chromatography studies and through the analysis of rheology data. The formation of LCBs by connecting the two growing polyolefin chains can facilitate the generation of polymers with molecular weights higher than that expected. Owing to the presence of LCBs, considerable shear thinning behavior is observed. Ethylene/1-octene copolymers can be prepared facilely to show almost the same shear thinning behavior with the commercial grade of low-density polyethylene, which is known to have a substantial amount of LCBs.
Keywords: Branched Polymer; Chain transfer; Chain transfer agents; Chain transfer polymerization; Commercial grade; Long chain branches; Long-chain branched polyolefins; Shear-thinning behavior